OPPORTUNITIES AND CHALLENGES OF ISLAMIC PHILANTHROPY IN THE DEVELOPMENT OF SHARIA ECONOMICS IN INDONESIA - Ash-Shiddiqy, Muhammad; Fitriyati, Intan Diana; Munajat, Makhrus; Wibowo, Muhammad Ghafur (Journal of International Conference Proceedings, 2024)
It can be said that the sharia-based economy in Indonesia has experienced rapid growth over the past few years, so it has bright future prospects. With the largest Muslim population in the world, strong government support, the growth of the Islamic finance industry, and global market potential, an economy based on sharia principles has a high opportunity to continue to grow and contribute to state revenues. But besides that, economic development with sharia principles also has several challenges that need to be faced, such as the lack of public understanding and infrastructure development that still needs to be improved. Based on this, researchers will conduct an analysis of the opportunities and challenges of sharia-compliant economic development in Indonesia. The results of this study are expected to make the public understand more about the future prospects of the Islamic economy in Indonesia. This study aims to find out about the opportunities and challenges of developing the Islamic economy in Indonesia with data acquisition techniques using secondary data obtained through journals, official websites, and other literature that has relevance to the topic